2011
DOI: 10.1029/2010jd014471
|View full text |Cite
|
Sign up to set email alerts
|

Decadal variability of aerosol optical depth in Europe and its relationship to the temporal shift of the North Atlantic Oscillation in the realm of dimming and brightening

Abstract: [1] Long-term aerosol optical depth (AOD) over Europe was analyzed from the Goddard Chemistry Aerosol Radiation and Transport (GOCART) model from . In particular, we studied the decadal sulfate AOD variability caused by large sulfur emissions from anthropogenic sources in Europe with a peak in [1988][1989]. Simulated annual means from 1985-2007 over the continent showed statistically significant declines of 69% and a maximum of 75% in eastern Europe. Seasonally, greatest variations occurred during winter and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 65 publications
6
38
0
Order By: Relevance
“…The insignificant trend of −8 % ± 5 % per decade observed at Uccle lies within the range of trends observed at other European stations. The long-term τ aer decrease over much of Europe is quite consistent with the supposed reversal from increasing to decreasing anthropogenic sulfur and black carbon emissions owing to the enactment of clean-air legislation in many countries (Mishchenko and Geogdzhayev, 2007;Chiaccio et al, 2011;Alpert et al, 2012;de Meij et al, 2012;Hsu et al, 2012;Nabat et al, 2013). This change occurred after 1988-1989, the time period when a maximum was reached in the emissions of sulfate aerosols over Europe (Chiaccio et al, 2011).…”
Section: Aerosol Optical Depth At 3201 Nmsupporting
confidence: 51%
See 2 more Smart Citations
“…The insignificant trend of −8 % ± 5 % per decade observed at Uccle lies within the range of trends observed at other European stations. The long-term τ aer decrease over much of Europe is quite consistent with the supposed reversal from increasing to decreasing anthropogenic sulfur and black carbon emissions owing to the enactment of clean-air legislation in many countries (Mishchenko and Geogdzhayev, 2007;Chiaccio et al, 2011;Alpert et al, 2012;de Meij et al, 2012;Hsu et al, 2012;Nabat et al, 2013). This change occurred after 1988-1989, the time period when a maximum was reached in the emissions of sulfate aerosols over Europe (Chiaccio et al, 2011).…”
Section: Aerosol Optical Depth At 3201 Nmsupporting
confidence: 51%
“…The long-term τ aer decrease over much of Europe is quite consistent with the supposed reversal from increasing to decreasing anthropogenic sulfur and black carbon emissions owing to the enactment of clean-air legislation in many countries (Mishchenko and Geogdzhayev, 2007;Chiaccio et al, 2011;Alpert et al, 2012;de Meij et al, 2012;Hsu et al, 2012;Nabat et al, 2013). This change occurred after 1988-1989, the time period when a maximum was reached in the emissions of sulfate aerosols over Europe (Chiaccio et al, 2011). Many scientists believe that the decadal changes in aerosols have influenced the amount of solar radiation reaching the surface of the Earth and that the decrease in aerosols has played a part in the switch from global dimming to global brightening, which occurred around 1980-1990(Augustine et al, 2008Chiaccio et al, 2011).…”
Section: Aerosol Optical Depth At 3201 Nmmentioning
confidence: 52%
See 1 more Smart Citation
“…This mechanism, however, is not confirmed by either GISS-E2 or NCAR-CESM1, and is therefore not robust and requires future investigation. Previous work relating aerosol forcing to North Atlantic circulation (Chiacchio et al, 2011;FischerBruns et al, 2009, Allen andSherwood, 2012) has been limited to single models and results have been inconclusive across studies. The impact of aerosols on the North Atlantic and Mediterranean climate (and the NAO) thus remains unclear, and 30 may warrant additional work with a larger model ensemble, with the diagnostics needed to probe the driving mechanisms more deeply, and to assess robustness in a more rigorous manner.…”
Section: Discussionmentioning
confidence: 99%
“…In that study greenhouse gas forcing was shown to be connected to the long-term downward trend in the amplitude of the annual cycle since 1950, whereas aerosol forcing was related to a nonlinear response, possibly in connection to the global dimming/brightening phenomenon (Wild 2009). However, in general the separation of aerosol forcing from atmospheric circulation variability is confounded by a broadly common trend throughout the latter decades of the twentieth century across the Northern Hemisphere in the aerosol-induced dimming and brightening effects and the North Atlantic Oscillation (NAO) and NAM (Chiacchio and Wild 2010;Chiacchio et al 2011). Furthermore, as pointed out by Qian and Zhang (2015), the signal-to-noise ratio in the amplitude of the annual cycle is much lower than is typically found in trends of mean temperature as a result of the same sign of signals in the winter and summer seasons.…”
Section: Introductionmentioning
confidence: 99%